Tampilan Produksi Susu Sapi Perah akibat Substitusi Rumput Gajah dengan Jerami Padi Amoniasi yang Disuplementasi Daun Ubi Kayu - suhardi suhardi (Universitas Boyolali, 2017)
The study aimed at evaluating the extent to which the dairy cow milk production appearance resulting from the substitution of Napier grass with ammoniated rice straw supplemented with cassava leaves and Soyxyl. The materials used in the study were: 16 dairy cows at 1st, 2nd, 3rd and 4th month lactations, Napier grass, concentrate, ammoniated rice straw, cassava leaves and bypass protein of the brand name Soyxyl. The paramof varians eters observed consisted of dry matter consumption, milk production, and blood glucose concentration. The data was analyzed statistically using analysis and when there was a significant impact it was then analyzed using Duncan’s multiple range test. The results of the study showed that there was not significant difference (P > 0.05) between T0, T1, T2 and T3 treatments on the dry matter consumption, milk production, and blood glukose concentration.Key words: Ammoniated rice rtraw, Cassava leaves, Napier grass, Protein supplement